A critical review on the performance of yielding supports in squeezing tunnels. (September 2021) - Wu, Kui; Shao, Zhushan; Qin, Su; Wei, Wei; Chu, Zhaofei
Highlights: Performance of four basic yielding elements is summarized. Two historical cases using supports with combined yielding elements are analyzed. Estimation method of rock squeezing potential is reviewed. Applicability of yielding supports is discussed. Recommendations for further research based on findings are provided. Abstract: The use of yielding supports has proven to be a highly effective measure for tunneling in squeezing grounds because of their agreement with the law of mechanical movement of rock mass. However, there is no well-established design method for yielding supports; hence, the purpose of this review is to discuss the recent advances in the development and application of these supports in squeezing tunnels. The review begins by briefly introducing the history of yielding supports and previous research work, and explaining the importance of investigating this issue. The causes of time-dependent deformation occurring in squeezing tunnels are then explained, and the definition and principle of yielding supports are introduced in Section 2 . The working characteristics and mechanical performance of four basic yielding elements energy-absorbing rockbolts, compressible layer, segmental shotcrete with highly deformable elements and steel arch with sliding connections are summarized in Section 3 . In Section 4, two case studies are used to illustrate tunnel performance when supported by yielding support systems combining different yielding elements. Section 5 includes a review of rock squeezing potential estimation methods and a summary of the applicability of yielding supports. Final comments on yielding supports are presented in Section 6, followed by recommendations for further research on these supports. Finally, a brief summary of the contents presented is provided in Section 7 .